2016
DOI: 10.1517/13543776.2016.1165210
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic compositions and uses of alpha1-antitrypsin: a patent review (2012 – 2015)

Abstract: A molecule no longer patentable per se, presents with novel clinical applications; its mechanism still unfolding. While modified protein sequences are patentable and potentially superior, they are burdened by regulatory setbacks. Thus, recent approaches in the context of AAT appear in patents that describe combinations with other drugs, redefined clinical subclasses, and unique recombinant entities, carefully skirting saturated areas of AAT patentology. It will be fascinating to follow technologies and creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Recent years have witnessed an expansion of potential clinical applications for hAAT treatment beyond that of straightforward augmentation therapy for genetic hAAT deficiency; these include type 1 diabetes ( 37 , 50 – 52 ), allogeneic and xenogeneic transplants ( 44 46 , 53 , 54 ), graft-versus-host disease ( 53 , 55 , 56 ), acute myocardial infarction ( 57 59 ), inflammatory bowel disease ( 52 , 60 ), rheumatoid arthritis ( 61 63 ), multiple sclerosis ( 41 ), and osteoporosis ( 64 , 65 ). Collectively, these represent an extension of earlier preclinical studies that portray hAAT as possessing anti-inflammatory and immunoregulatory properties ( 3 , 4 , 26 , 35 ).…”
Section: Discussionmentioning
confidence: 54%
“…Recent years have witnessed an expansion of potential clinical applications for hAAT treatment beyond that of straightforward augmentation therapy for genetic hAAT deficiency; these include type 1 diabetes ( 37 , 50 – 52 ), allogeneic and xenogeneic transplants ( 44 46 , 53 , 54 ), graft-versus-host disease ( 53 , 55 , 56 ), acute myocardial infarction ( 57 59 ), inflammatory bowel disease ( 52 , 60 ), rheumatoid arthritis ( 61 63 ), multiple sclerosis ( 41 ), and osteoporosis ( 64 , 65 ). Collectively, these represent an extension of earlier preclinical studies that portray hAAT as possessing anti-inflammatory and immunoregulatory properties ( 3 , 4 , 26 , 35 ).…”
Section: Discussionmentioning
confidence: 54%
“…The study places emphasis on function- and outcome-oriented analyses of treatment, a particularly important entity when considering that hAAT is entering an era of drug-repurposing toward an extended list of clinical indications (Lewis, 2012; Lior et al, 2016). More studies are to be undertaken to optimize treatment protocols relevant to diseases other than AATD.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials presently address the potential benefit of AAT therapy to individuals without AATD, including islet and lung transplantation, type 1 diabetes (T1D), graft-versus-host disease, acute myocardial infarction, and cystic fibrosis (Lior et al, 2016). In the case of T1D clinical trials, the initial dosing plan for assessing islet protection by AAT was directly borrowed from the long-standing protocols of AAT augmentation therapy for AATD patients, e.g., weekly infusions of 60–80 mg/kg plasma-derived affinity-purified human AAT (Balbi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“… 121 There is a theoretical basis and some supporting data for the potential benefit of AAT in other conditions characterized by excessive neutrophilic inflammation such as inflammatory bowel disease, rheumatoid arthritis and postoperative systemic inflammatory response syndrome (SIRS). 122 For example, Daemen et al have demonstrated that AAT mitigates renal reperfusion injury in mice via reduced TNF-α and neutrophil influx. 123 Kaner et al have shown that transgenic mice expressing the human AAT gene have reduced levels of liver and pancreatic dysfunction compared to wild-type mice in an SIRS model, as well as improved survival at 24 hours.…”
Section: Positive Effects Of Aat As Treatment In Other Lung Diseasesmentioning
confidence: 99%